Profile of Students’ Mathematical Beliefs at State Junior High School 1 Palu in Solving Algebra Problems Viewed from Learning Styles - Nurhidayah Nurhidayah; Pathuddin Pathuddin; Fajriani Fajriani; Mubarik Mubarik (Journal of Educational Sciences, 2026)
This study aims to describe the profile of students’ mathematical beliefs in solving algebra problems at state junior high school 1 Palu, viewed from their learning styles. Mathematics learning, particularly algebra, often faces obstacles due to its abstract symbolic nature, which affects students’ confidence. Self-efficacy, as part of mathematical belief, plays an important role in students’ persistence and strategies when solving problems. This research employed a qualitative approach with a descriptive design. Data were collected through a learning style questionnaire, written algebra tests, and semi-structured interviews. The analysis was conducted based on self-efficacy indicators, namely magnitude, strength, and generality. The results showed that students with a visual learning style had high self-efficacy, confidence in constructing equations, persistence in solving problems, and verification of answers. Students with an auditory learning style demonstrated low self-efficacy, doubts in algebraic manipulation, and lack of confidence in generalizing strategies. Meanwhile, students with a kinesthetic learning style exhibited high self-efficacy, confidence in representing variables, persistence in solving problems, and ability to recheck results. These findings emphasize that learning styles influence students’ mathematical beliefs, particularly self-efficacy, in algebra problem solving. The study concludes that aligning instructional strategies with students’ learning styles can strengthen self-efficacy and foster positive mathematical beliefs.